Can connective use differentiate between children with and without specific language impairment?. Issue 1 (February 2015) - Tribushinina, Elena; Dubinkina, Elena; Sanders, Ted
The ability of language-impaired children to maintain coherence by using discourse connectives has so far been assessed by quantitative measures. This study is a first attempt to scrutinize the quality of connective use in specific language impairment (SLI). The authors investigate whether Russian-speaking children reveal sensitivity to the subtle discourse-organizational distinctions between the quasi-synonymous connectives i 'and' and a 'and/but' in a narrative task. Study 1 compared connective use by 7-year-olds with and without SLI. The results demonstrate that connective frequencies do not differentiate between the two groups, but language-impaired children more often use connectives in a way that violates causal relations in the story. Study 2 assessed connective production by the same SLI participants 16 months later and also tested understanding of causal chains in a follow-up interview. The error rates remained high. These errors were not due to poor understanding of the story, since the language-impaired children answered the causal questions in the follow-up interview as well as their unimpaired peers did.